The Influence Of The Tourism Sector On The Economy Of The Special Capital Province Of Jakarta: Input Output Analysis - Muhammad Farouq Rosyadi; Aviliani Aviliani; Muhammad Iqbal (SEAN Institute, 2023)
The purpose of this research is to analyze the role of the tourism sector in the economy of DKI Jakarta Province. The method used is Input-Output analysis. The data used is secondary data derived from the Total Input-Output Table on the basis of 2012 DKI Jakarta Provincial Buyer Prices, classification of 72 sectors, which have been updated based on 2018 GRDP data. The analysis consists of linkage analysis, distribution impact analysis, and multiplier analysis. From the analysis, it can be seen that the transportation and warehousing sub-sectors have the highest value for each multiplier value. It can be said that this sub-sector is a priority sub-sector which can be used as a reference for the development of the tourism sector in DKI Jakarta Province because it is the sub-sector with the most potential to increase people's income. Development in this sub-sector can reduce poverty and unemployment in DKI Jakarta.